Deciphering the Link Between Hyperhomocysteinemia and Ceramide Metabolism in Alzheimer-Type Neurodegeneration - Le Stunff, Hervé; Véret, Julien; Kassis, Nadim; Denom, Jessica; Meneyrol, Kelly; Paul, Jean-Louis; Cruciani-Guglielmacci, Céline; Magnan, Christophe; Janel, Nathalie (Frontiers in Neurology, 2019)
While aging is clearly the strongest risk factor for Alzheimer’s disease (AD), emerging data suggest that dyslipidemic states can either contribute to or serve as co-factors in its pathogenesis. AD could be regarded as a metabolic disease mediated by peripheral insulin resistance disorders. Insulin resistance is associated with dyslipidemia, which results in increased hepatic ceramide generation. Progressive hepatic steatosis incites inflammation and pro-inflammatory cytokine activation, which is mediated by the increased ceramides production. Ceramides accumulate in cells due to disturbances in sphingolipid metabolism and upregulated expression of enzymes involved in ceramide synthesis. Cytotoxic ceramides and related molecules generated in liver promote insulin resistance, traffic through the circulation following injury or cell death caused by local liver inflammation, and due to their lipid soluble nature, cross the blood-brain barrier and exert neurotoxic effects by impairing insulin signaling and activating pro-inflammatory cytokines. These abnormalities establish or help propagate a cascade of neurodegeneration associated with oxidative stress and ceramide generation, which exacerbate brain insulin resistance, cell death, myelin degeneration, and neuro-inflammation. Therefore, toxic lipids generated in liver can cause neurodegeneration. Elevated homocysteine level is a risk factor for AD pathology and is closely associated with metabolic diseases and non-alcoholic fatty liver disease. Results suggest the existence of a homocysteine/ceramides signaling pathway which suggest that homocysteine toxicity may be at least partly mediated by intracellular ceramide accumulation via a direct consequence of stimulation of ceramide synthase. In this article, we briefly examined the role of homocysteine and ceramide metabolism linking metabolic diseases and non-alcoholic fatty liver disease to AD. We therefore analyzed the expression of mainly enzymes implicated in ceramide and sphingolipid metabolism and demonstrated deregulation of de novo ceramide synthesis and S1P metabolism in liver and brain of hyperhomocysteinemic mice.